2019
DOI: 10.1016/j.clbc.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Anthracycline Use in Hormone Receptor Positive, Early-Stage Breast Cancer

Abstract: In this study we investigated factors associated with prescribing patterns for an anthracycline-based chemotherapy in hormone receptor-positive stage I to III breast cancer. We carried out a retrospective analysis of the Michigan Breast Oncology Quality Initiative data set of 17,788 women with stage I to III estrogen receptor/progesterone receptor-positive HER2/neu-negative invasive breast cancer. Patients with a high recurrence score and lymph node-positive status were just as likely to receive an anthracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
1
2
0
1
Order By: Relevance
“…Unfortunately, few studies addressed this question, and more investigations are needed. In a study on hormone receptor‐positive early‐stage breast cancer, ABC was administered more often to young patients (40% of the patients <65 years), to the ones with stage III disease (69%) or higher 21‐gene recurrence scores, and positive lymph nodes encouraged the selection of ABC in the absence of high recurrence scores 9 . As regard the clinicopathological characteristics, the results of this study were highly compatible with that of our analysis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Unfortunately, few studies addressed this question, and more investigations are needed. In a study on hormone receptor‐positive early‐stage breast cancer, ABC was administered more often to young patients (40% of the patients <65 years), to the ones with stage III disease (69%) or higher 21‐gene recurrence scores, and positive lymph nodes encouraged the selection of ABC in the absence of high recurrence scores 9 . As regard the clinicopathological characteristics, the results of this study were highly compatible with that of our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Currently, regimens that include doxorubicin are listed in The National Comprehensive Cancer Network guidelines as an alternative option in all risk levels and stages of breast cancer except for the lowest risk and early‐stage breast cancer 3 . However, the use of other anticancer agents has led to the study of a greater number of combinations of chemotherapeutic drugs in specific patients, and consequently anthracycline‐based chemotherapy (ABC) has been in decline for decades 8,9 . Additionally, anthracyclines exert remarkable adverse effects and among them, cardiotoxicity is the main one.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the available evidence, a retrospective real-world analysis including 17 788 patients with HR-positive, HER2-negative early BC candidate to receive chemotherapy based on a 21-gene assay showed that anthracyclines are prescribed more often to younger patients, with higher-stage tumors and with higher 21-gene recurrence scores, suggesting the tendency in clinical practice of avoiding the potential serious complications associated with anthracycline treatment in patients least likely to receive benefit. 39 …”
Section: The Case Against Anthracyclines In the Treatment Of Early Br...mentioning
confidence: 99%
“…Los autores señalaron que la prescripción de las antraciclinas fue más frecuente aún en pacientes con RB o RI con ganglios positivos; sin embargo, el estado ganglionar axilar no parece haber sido un factor de selección del tratamiento en el grupo con RA. 26 La esencia del estudio publicado por Paik 18 fue validar, de manera prospectiva, la capacidad de la prueba de 21 genes para predecir el riesgo de recurrencia en casos con ganglios negativos y RE positivos tratados con tamoxifeno adyuvante, sus resultados rápidamente derivaron en considerar que el grupo RA debía recibir quimio y endocrinoterapia y, ante la carencia de información, la quimioterapia seguida de terapia hormonal era indicada en casos con RI y ganglios positivos. 27 TAILORx 20 fue un ensayo controlado, prospectivo, el cual analizó 10,253 mujeres de 18 a 75 años, con CM, RH positivos, HER2 negativo y ganglios axilares negativos, el cual fue dirigido para evaluar la no inferioridad de la terapia endocrina frente a la quimioterapia adyuvante en casos con RI (puntuación [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Wwwmedigraphicorgmxunclassified